South (S)- and North (N)-Methanocarba-7-Deazaadenosine Analogues as Inhibitors of Human Adenosine Kinase - Toti, Kiran S. (J Med Chem, 2016)
Adenosine kinase (AdK) inhibitors raise endogenous adenosine levels, particularly in disease states, and have potential for treatment of seizures, neurodegeneration, and inflammation. Based on the South (S) ribose conformation and molecular dynamics (MD) analysis of nucleoside inhibitors bound in AdK X-ray crystallographic structures, (S)- and North (N)-methanocarba (bicyclo[3.1.0]hexane) derivatives of known inhibitors were prepared and compared as human (h) AdK inhibitors. 5′-Hydroxy (34, MRS4202 (S); 55, MRS4380 (N)) and 5′-deoxy 38a (MRS4203 (S)) analogues, containing 7- and N(6)-NH phenyl groups in 7-deazaadenine, robustly inhibited AdK activity (IC(50) ~100 nM), while the 5′-hydroxy derivative 30 lacking the phenyl substituents was weak. Docking in the hAdK X-ray structure and MD simulation suggested a mode of binding similar to 5′-deoxy-5-iodotubercidin and other known inhibitors. Thus, a structure-based design approach for further potency enhancement is possible. The potent AdK inhibitors in this study are ready to be further tested in animal models of epilepsy.